IMPLEMENTASI PERATURAN DAERAH NOMOR 1 TAHUN 2017 TENTANG PENCEGAHAN DAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOTIKA (P4GN) TERHADAP PENYALAHGUNAAN NARKOTIKA - Rizki Ahmad Fauzi; Yaqub Cikusin; Hayat Hayat (Journal Publicuho, 2022)
This research is motivated by the problems encountered in the application of regional regulation number 1 of 2017 which contains norms against drug abuse and the like, this study aims to find out about the implementation of regional regulation number 1 of 2017 concerning the prevention and eradication of abuse and illicit trafficking. narcotics (P4GN) against narcotics abuse, (Policy Study on the Guidance and Supervision of Adolescents at the National Narcotics Agency of Malang Regency). In this study the authors used descriptive qualitative methods, using a qualitative approach. where researchers use information sources in the field to find information as deep as possible. With this approach, the author can describe the conditions and situations that exist in the field based on the data sources obtained through observation, interviews, and documentation techniques. Research informants in this study were BNN officers in Malang Regency and patients infected with drugs. The place of this research is located at BNN Pakis, Malang Regency. The results of the study indicate that the implementation of regional regulation number 1 of 2017 concerning the prevention and eradication of abuse and illicit trafficking of narcotics (P4GN) against narcotics abuse has been implemented well, but there are still some obstacles encountered in the application of existing regulations such as facilities, funds, and new tricks in marketing drugs.